A Species-Specific Strategy for the Identification of Hemocoagulase Agkistrodon halys pallas Based on LC-MS/MS-MRM - Xian, Ruiqing; Wang, Congcong; Gong, Liping; Hang, Baojian; Wang, Weijian; Zhang, Xunjie; Du, Hongmin; Wang, Fengshan; Shi, Feng (Frontiers in Molecular Biosciences, 2022)
Hemocoagulase Agkistrodon halys pallas is a complex mixture composed of snake venom thrombin-like enzymes (svTLEs) and small amounts of thrombokinase-like enzymes. It has been widely used as a hemostatic with rapidly growing marketing due to its advantage of localized clotting fibrinogen other than systemic coagulation. However, svTLEs from different species have various structures, functions and hemostatic mechanisms. To ensure the efficacy and safety of Hemocoagulase Agkistrodon halys pallas, an exclusive and sensitive method has been developed to identify specific marker peptide based on liquid chromatography-tandem mass spectrometry with multiple reaction monitoring (LC-MS/MS-MRM) mode. By combining transcriptomics and proteomics, a series of species-specific peptides of Agkistrodon halys pallas were predicted and examined by LC-MS/MS. After reduction, alkylation and tryptic digestion were performed on Hemocoagulase Agkistrodon halys pallas, target peptide TLCAGVMEGGIDTCNR was analyzed by LC-MS/MS-MRM. It offers a new and effective approach for the quality control of Hemocoagulase Agkistrodon halys pallas products. This method is superior to the current assays in terms of sensitivity, specificity, precision, accuracy and throughput. The strategy can also be applied in studying other important protein-based medicines.